Dimerization of Doxorubicin Causes Its Precipitation - Yamada, Yuji (ACS Omega, 2020)
[Image: see text] Doxorubicin (DOX) is commonly used in chemotherapy and biomedical research because of its potent anticancer activity. Although DOX is water soluble, it precipitates when interacting with buffers, such as phosphate-buffered saline, or with drugs such as 5-fluorouracil (5-FU) and heparin. This study reports that DOX precipitates in neutral buffers and 5-FU solution because of the formation of covalently bonded DOX dimers. Additionally, this study proposes a structure for the DOX dimer and a mechanism for dimerization on the basis of mass spectrometry in combination with an experiment to establish the reaction model. The DOX dimer/precipitate formation might be an important phenomenon, considering the frequent use of DOX in chemotherapy and biomedical research.